Improving Work Productivity Through Training, Discipline And Communication At PT. Linewin - Martin; Dewi Rafiah Pakpahan (Publisher Cv. Inara, 2020)
The purpose in this study is to analyze the influence of both partial and simultaneous training, discipline and communication on productivity. This research was conducted on PT. Linewin selected 117 production employees to sample. data collection using questionnaires with data analysis using SPSS 22. The results showed that training, discipline and communion had a positive and significant effect on productivity in PT. Linewin. Discipline variables have the most dominant influence in improving employee work productivity in PT. Linewin. Furthermore, the result of a determination coefficient of 69.1% of productivity variables can be explained by variations in training, discipline and communication variables and the remaining 40.9% is another variable not studied in this study